Accelerating cardiovascular research: recent advances in translational 2D and 3D heart models. (4th August 2022) - Mohr, Elisa; Thum, Thomas; Bär, Christian
Abstract : In vitro modelling the complex (patho‐) physiological conditions of the heart is a major challenge in cardiovascular research. In recent years, methods based on three‐dimensional (3D) cultivation approaches have steadily evolved to overcome the major limitations of conventional adherent two‐dimensional (2D) monolayer cultivation. These 3D approaches aim to study, reproduce or modify fundamental native features of the heart such as tissue organization and cardiovascular microenvironment. Therefore, these systems have great potential for (patient‐specific) disease research, for the development of new drug screening platforms, and for the use in regenerative and replacement therapy applications. Consequently, continuous improvement and adaptation is required with respect to fundamental limitations such as cardiomyocyte maturation, scalability, heterogeneity, vascularization, and reproduction of native properties. In this review, 2D monolayer culturing and the 3D in vitro systems of cardiac spheroids, organoids, engineered cardiac microtissue and bioprinting as well as the ex vivo technique of myocardial slicing are introduced with their basic concepts, advantages, and limitations. Furthermore, recent advances of various new approaches aiming to extend as well as to optimize these in vitro and ex vivo systems are presented.